Problem Based Learning: Developing competency in knowledge integration in health design - Sellen, Katherine (Design and Technology Education: An International Journal, 2018)
Different communities, organizations, and people hold different views on their own and others’ wellbeing. It is often challenging to balance different perspectives during the design process when the truth of medicine is competing with the truth of social media and the everyday experience of wellbeing of patients, caregivers, family and friends. In the context of the Masters of Health Design at OCAD University (OCAD U), we develop students’ competency in working with truth through challenging students to engage with multiple ‘truths’ in the design process, engaging deliberately in identifying and working with multiple truth regimes as part of a problem based learning approach. This includes how truth regimes impact the understanding of a challenge area, techniques for engaging with stakeholders, communicating and developing concepts, and the process of seeking and working with feedback for refining and iterating, and finally in communicating project solutions. By engaging in problem based learning, students are exposed to the real challenges of different stakeholder perspectives and in particular how different truth regimes serve to impact what counts as legitimate knowledge and legitimate knowledge representation.